Vitamin B6 Alleviates Lipopolysaccharide-induced Myocardial Injury by Ferroptosis and Apoptosis Regulation - Shan, Meirong; Yu, Xujie; Li, Yajie; Fu, Changning; Zhang, Cheng (Frontiers in Pharmacology, 2021)
Vitamin B6 (VitB6), a water-soluble vitamin, includes pyridoxine, pyridoxal, pyridoxamine and their phosphorylated forms. In this study, we demonstrated that VitB6 improved myocardial injury induced by lipopolysaccharide (LPS). And we further testified that VitB6 suppressed LPS-induced oxidative stress and lipid peroxidation which led to ferroptosis and apoptosis in vivo and in vitro. Moreover, we found that VitB6 regulated the expression of iron regulatory proteins which maintain intracellular iron homeostasis. To confirm that VitB6 could inhibit LPS-induced ferroptosis and apoptosis, we pretreated mice with ferrostatin-1 (Fer-1) and emricasan that efficiently mimicked pharmacological effect of VitB6 and raised the survival rate of the mice challenged with high dose of LPS. VitB6 regulated the expression of apoptosis-related proteins and iron regulatory proteins induced by LPS; yet, VitB6 mediated the expression of Nrf2, transcription factor NF-E2-related factor 2, which promoted the expression of antioxidant enzymes and further restrained the LPS-induced ferroptosis and apoptosis. This study indicated a novel therapy to relieve myocardial injury induced by LPS.